Lettere di Margherita Guidacci a Mladen Machiedo - Lombardi, Sara (Biblioteca di Studi di Filologia Moderna, 2015)
The collection of Lettere di Margherita Guidacci a Mladen Machiedo reinterprets the author's cultural and poetic path in the light of the affinities with the Catholic writers from Florence, the bond with her area of origin, the Mugello, the English studies, the critical work, the constant loyalty to poetry (from the poetic beginnings with La sabbia e l'angelo in 1946, until her last test, Anelli del tempo in 1993). This volume collects the letters that, between 1968 and 1989, Guidacci wrote to Machiedo, a Croatian poet, translator and distinguished scholar of Italian studies. The two were bonded by common cultural interests and a deep friendship. The richly annotated correspondence makes it possible to shed light on the genesis of her works, and allows the recovery of some poetic texts which are difficult to find in Italy.